A-1: TEACHING ARABIC LANGUAGE FOR SPECIFIC PURPOSES: تعليم اللغة العربية للناطقين بغيرها لأغراض خاصة - Akram, Aliya; Ahmad, Zaheer (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2022)
Arabic Language is primarily regarded as the language of the Quran and the Sunnah. Arabic is, therefore, learnt and spread all over the globe. However, Arabic is also a cultural heritage shared by all Islamic Nations. The idea of teaching Arabic for specific purposes is comprehensively discussed in the academic sphere these days. Although the number of learners of Arabic is increasing consistently, yet their purposes vary. These include religious purpose, international trade, diplomatic purpose, better livelihood in the Arab world etc. By virtue of this high demand for learning Arabic, numerous efforts have been established all over the world. This article aims at focusing on the current efforts of the Arabic Language teaching for specific purposes worldwide.